2018
DOI: 10.1080/16549716.2018.1496889
|View full text |Cite
|
Sign up to set email alerts
|

Broken dreams of a better life in Sweden: Thai women’s lived experiences of intimate partner violence by Swedish men in international marriages

Abstract: Background: Intimate partner violence by men against women has detrimental effects on equality, health and integration. Migrated and ‘imported’ wives experience an increased risk of intimate partner violence. Objectives: The purpose of this study was to explore Thai immigrant women’s lived experiences of intimate partner violence in Sweden. Method: Semi-structured interviews based on the critical incident technique with specific questions about experiences of male-to-female intimate partner violence were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…According to Fawcett (2011), Neuman (1995), interpersonal stressors, such as family responsibilities or difficulties, are tension-producing incentives that have the potential to interrupt an individual's systemic ability to create wellness and health. The interviewed Thai women that had immigrated to Sweden; longed for wealthier lives, often trying to leave poverty and bad situations behind (Pongthippat et al, 2018;Ekblad and Kastrup, 2013;Hjern, 2012). In the present study, half the interviewees were well educated, which suggests that middle-class women with formal educations also participate in marriage migration looking for other living conditions, as described by Kanchanachitra et al (2014).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…According to Fawcett (2011), Neuman (1995), interpersonal stressors, such as family responsibilities or difficulties, are tension-producing incentives that have the potential to interrupt an individual's systemic ability to create wellness and health. The interviewed Thai women that had immigrated to Sweden; longed for wealthier lives, often trying to leave poverty and bad situations behind (Pongthippat et al, 2018;Ekblad and Kastrup, 2013;Hjern, 2012). In the present study, half the interviewees were well educated, which suggests that middle-class women with formal educations also participate in marriage migration looking for other living conditions, as described by Kanchanachitra et al (2014).…”
Section: Discussionsupporting
confidence: 52%
“…This unreflected view of marriage migration is also comparable with how some brides hope for what western life might include such as satisfying desires, aspirations and imaginings of a loving marital relationship and economic migration (Sunanta and Angeles, 2013). Nevertheless, transnational marriages have an increased risk of finding themselves in strained situations due to discrimination, intimate partner violence and continuous economic problems (Pongthippat et al, 2018;Ekblad and Kastrup, 2013;Hjern, 2012), including an increased risk of becoming involved in typified sex labour work (Mix, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…Family difficulties, as a primary source of stress, was also reported in Australia among Thai female migrants [23]. Another Swedish study found that relationship breakups were stressful for Thai migrant women [21]. In our study, this finding is interesting from a temporal perspective as we asked participants about stress experience in their daily life and at the time of the interviews most were already separated or divorced.…”
Section: Discussionmentioning
confidence: 66%
“…From neighboring Sweden, a study with Thai migrant wives reported women’s experiences of physical, psychological and economic IPV and identified that unequal power relations in Thai international marriages leave women vulnerable [21]. Another Swedish study found that exposure to IPV among Thai women was associated with poor mental health [22].…”
Section: Introductionmentioning
confidence: 99%
“…Research on Swedish Asians is tiny and fragmentary in light of how big the minority is, and for the most part, it consists of social medicine and social work studies of Asian women who live together with white men (Åkerman 2019;Fernbrant et al 2014Fernbrant et al , 2017Hedman 2009;Hedman, Nygren & Fahlgren 2009;Lundberg 1999Lundberg , 2000Pongthippat et al 2018).…”
Section: Swedish Research On Asians Asians As a Model Minority And The Non-white Swedish Literaturementioning
confidence: 99%